Outcome of acute respiratory distress syndrome requiring extracorporeal membrane oxygenation in Covid‐19 or influenza: A single‐center registry study. Issue 6 (18th December 2020) - Jäckel, Markus; Rilinger, Jonathan; Lang, Corinna Nadine; Zotzmann, Viviane; Kaier, Klaus; Stachon, Peter; Biever, Paul Marc; Wengenmayer, Tobias; Duerschmied, Daniel; Bode, Christoph; Staudacher, Dawid Leander; Supady, Alexander
Abstract: Veno‐venous extracorporeal membrane oxygenation (V‐V ECMO) is used to sustain blood oxygenation and decarboxylation in severe acute respiratory distress syndrome (ARDS). It is under debate if V‐V ECMO is as appropriate for coronavirus disease 2019 (Covid‐19) ARDS as it is for influenza. In this retrospective study, we analyzed all patients with confirmed SARS‐CoV‐2 or influenza A/B infection, ARDS and V‐V ECMO, treated at our medical intensive care unit (ICU) between October 2010 and June 2020. Baseline and procedural characteristics as well as survival 30 days after ECMO cannulation were analyzed. A total of 62 V‐V ECMO patients were included (15 with Covid‐19 and 47 with influenza). Both groups had similar baseline characteristics at cannulation. Thirty days after ECMO cannulation, 13.3% of all patients with Covid‐19 were discharged alive from our ICU compared to 44.7% with influenza ( P  = .03). Patients with Covid‐19 had fewer ECMO‐free days (0 (0‐9.7) days vs. 13.2 (0‐22.1) days; P  = .05). Cumulative incidences of 30‐day‐survival showed no significant differences (48.6% in Covid‐19 patients, 63.7% in influenza patients; P  = .23). ICU treatment duration was significantly longer in ARDS patients with V‐V ECMO for Covid‐19 compared to influenza. Thirty‐day mortality was higher in Covid‐19, but not significant. Abstract : Patients with severe Covid‐19 supported with V‐V ECMO are less likely to be discharged from ICU within 30 days after initiation of V‐V ECMO than patients with influenza virus infection and V‐V ECMO. Hospital mortality was higher in patients with Covid‐19, but not significant.